Experiential Interventions for Clients with Genital Herpes - Cummings, Anne L. (Canadian Journal of Counselling and Psychotherapy, 2007)
Prevalent counselling approaches for individuals with genital herpes have primarily focused on short-term individual and group interventions to reduce stress levels and increase coping strategies for dealing with the disease. This article explores the potential benefits of incorporating concepts and interventions from experiential therapy to help clients deal with the more psychosocial difficulties in learning to live with this disease. Experiential counselling interventions of two-chair dialogue, empty chair, and metaphor are suggested for helping clients work through the emotional sequelae of genital herpes. A case illustration is presented of a young, female, Korean, university student who received 18 sessions of counselling which focused on dealing with the psychosocial aspects of the disease.